Оптимальне проектування параметрів гірничозбагачувальних підприємств для раціонального освоєння цінних родовищ України - Гріньов, В.Г.; Хорольський, А.О. (Физико-технические проблемы горного производства, 2019)
Мета. Вирішити проблему ефективного освоєння родовищ рідкісних і благородних металів шляхом створення технології оптимального проектування.
Методика. Для моделювання процесу освоєння конкретного родовища застосовано методи динамічного програмування, вибір раціонального обсягу виробництва здійснено шляхом порівняння граничних витрат і доходу та врахування екологічного аспекту освоєння родовища.
Результати. Наведено результати моделювання стратегії освоєння золоторудного родовища спеціалізованою програмою динамічного програмування, проілюстровані розрахунки раціонального об’єму видобутку металу на реальному родовищі і наведено приклад побудови альтернативного варіанту екологічної стратегії освоєння родовищ золота.
Наукова новизна. Вперше запропоновано методики і результати досліджень по оптимальному проектуванню параметрів експлуатації родовищ цінних корисних копалини України, які є основою методології рішення складних завдань оптимізації параметрів гірничо-збагачувального підприємства та відповідають сучасному рівню інформаційних технологій.
Практична значимість. Запропоновано технологію оптимального проектування гірничозбагачувальних підприємств, яка є інноваційною продукцією з реалізації ефективного освоєння родовищ корисних копалини та базується на наукомістких процедурах ухвалення рішень. Цель. Решить проблему эффективного освоения месторождений редких и благородных металлов путем создания технологии оптимального проектирования.
Методика. Для моделирования процесса освоения конкретного месторождения применено методы динамического программирования, выбор рационального объема производства осуществлено путем сравнения предельных издержек и дохода и учета экологического аспекта освоения месторождения.
Результаты. Приведены результаты моделирования стратегии освоения золоторудного месторождения специализированной программой динамического программирования, проиллюстрированные расчеты рационального объема добычи металла на реальном месторождении и приведен пример построения альтернативного варианта экологической стратегии освоения месторождений золота.
Научная новизна. Впервые предложены методики и результаты исследований по оптимальному проектированию параметров эксплуатации месторождений ценных полезных ископаемых Украины, которые являются основой методологии решения сложных задач оптимизации параметров горно-обогатительного предприятия и соответствуют современному уровню информационных технологий.
Практическая значимость. Предложена технология оптимального проектирования горно-обогатительных предприятий, которая является инновационной продукцией по реализации эффективного освоения месторождений полезных ископаемых и базируется на наукоемких процедурах принятия решений. Purpose. To solve the problem of efficient development of rare and precious metals by creating optimal design technology and propose a new approach to the design of layout of ore deposits with reserves of rare and precious metals.
Methods. To model the process of development of a particular field used methods of dynamic programming, the choice of rational production volume made by comparing marginal costs and income and taking into account the environmental aspect of the development of the field. The paper presents numerous specifications of the development of valuable ore reserves, which can be displayed in a mathematical model of the state of reserves throughout the entire period operation of fields. Evaluate and make a choice in different geological, territorial and social conditions, taking into account the great variety of forms of ore bodies and high value of the mineral, possibly based on dynamic programming.
Findings. The results of modeling the strategy of development of gold deposits with a specialized program of dynamic programming, the calculations of the rational volume of metal production at the real field and an example of constructing an alternative version of the ecological strategy for the development of gold deposits are presented. Modern methods are described for determining the profitability of exploiting real reserves of gold field, which show the possibilities of efficient development of high-grade ore resources, as well as creating powerful anchor projects for building up our own mineral resources sector of Ukraine.
Originality. It has been a model of changes in the state of the balance reserves of home made fields is describes, taking into account the current and compulsive antecedents for dynamic programming. A method of optimizing the model is given and software calculations are recommended.
Practical implications. We developed the system for decision-making support, which allows optimizing operational parameters of layout of ore deposits with reserves of rare and precious metals.